A review of the benefits of electronic detonators - Cardu,Marilena (2013)
Computerized drilling and the electronic timing of detonations are two technological breakthroughs which have had an important role in updating drilling and blasting excavation methods, although the electronic timing of detonators is still a comparatively infrequent technical solution to precision blasting problems. On the basis of an extensive collection of published cases, this paper reviews the successes achieved and the main expected advantages from the electronic ignition devices. After describing the primary characteristics of these detonators, some elements will be considered, in order to better understand their applications in different conditions, both in open pit and underground sites: extension of the time delay number, freedom in the choice of time intervals between detonations, timing accuracy, reduction of vibrations, control of back-break and fragmentation. The results are compared to those obtained by pyrotechnical timing devices, and summarized in the concluding remarks.